'Female Heroes': Celebrity Executives as Postfeminist Role Models. (13th July 2018) - Adamson, Maria; Kelan, Elisabeth K.
Abstract: This paper explores the significance of contemporary celebrity businesswomen as role models for women aspiring to leadership in business. We explore the kind of gendered ideals they model and promote to women through their autobiographical narratives, and analyse how these ideals map against a contemporary postfeminist sensibility to further understand the potential of these role models to redress the under‐representation of women in management and leadership. Our findings show that celebrity businesswomen present a role model that we call the 'female hero', a figure characterized by 3Cs: confidence to jump over gendered barriers; control in managing these barriers; and courage to push through them. We argue that the 'female hero' role model is deeply embedded in the contemporary postfeminist sensibility; it offers exclusively individualized solutions to inequality by calling on women to change themselves to succeed, and therefore has limited capacity to challenge the current gendered status quo in management and leadership. The paper contributes to current literature on role models by generating a more differentiated and socially situated understanding of distant female role models in business and extending our understanding of their potential to generate sustainable and long‐term change in advancing gendered change in management and leadership.